PENGARUH DISIPLIN KERJA, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INERVENING PADA SEKRETARIAT DAERAH KABUPATEN PASAMAN BARAT - Al Faisal, Aldy; Elfiswandi, Elfiswandi; Yeni, Fitri (Jurnal Daya Saing, 2026)
This study aims to determine the effect of Work Discipline, Compensation, and Work Environment on Employee Performance with Work Motivation as an intervening variable at the Regional Secretariat of West Pasaman Regency. The method used is multiple linear regression analysis and path analysis, by distributing 160 questionnaires. The results showed that there is a positive and significant effect of Work Discipline on Work Motivation, there is a positive and significant effect of Compensation on Work Motivation, there is a positive and significant effect of Work Climate on Work Motivation at the Regional Secretariat of West Pasaman Regency. There is a positive and significant effect of Work Discipline on Employee Performance, there is a positive and significant effect of Compensation on Employee Performance, there is no effect of Work Environment on Employee Performance, there is a positive and significant effect of Work Motivation on Employee Performance at the Regional Secretariat of West Pasaman Regency. Work Motivation is not able to mediate the effect of Work Discipline on Employee Performance, Work Motivation is not able to mediate the effect of Work Environment on Employee Performance, Work Motivation is able to mediate the effect of Compensation on Employee Performance at the Regional Secretariat of West Pasaman Regency. Finally, the author suggests that the Regional Secretariat of West Pasaman Regency further enhance Work Motivation as it has the most dominant influence on Employee Performance in West Pasaman Regency